Fabrication of fluorapatite cement as an anti-caries agent based on calcium phosphate cement - Saidin, Annisatul Arrufaidhah; Cahyanto, Arief; Takarini, Veni (Universitas Padjadjaran, 2021)
Introduction: Many research proves that fluorapatite cement is one of the materials in dentistry that can restore and treat severe carious lesions. The current research was aimed to study the chemical reaction of calcium phosphate cement (CPC), calcite, and calcium fluoride as a base in fabricating the fluorapatite cement as an anti-caries agent. Methods: The type of research is a descriptive method. The preparation of DCPA was initially performed by measuring 0.2g of DCPA powder which was prepared for 15 samples. Fluorapatite was fabricated using dicalcium phosphate anhydrous (DCPA), calcite (CaCO3) as the precursor to form carbonate apatite crystal, and calcium fluoride (CaF2). CaF2 will be mixed into sodium dihydrogen phosphate (NaH2PO4) with different percentages, 1%, 5%, and 10%. The samples were then incubated for 24 hours at 37˚C under 100% moisture condition. X-Ray Diffraction (XRD) characterization will be conducted to determine the phase composition and crystallinity of fluorapatite. In addition, the samples were analyzed with the Fourier Transform Infrared Spectroscopy (FTIR) examination to determine the crystal functional group. Results: All of the samples showed a satisfactory setting reaction. The XRD characterization results showed the formation of the crystal apatite phase at 32.43˚ and 32.83˚. The FTIR results indicated the stretching vibration of the fluoride compound at 1400 cm-1. The intensity formation of the apatite crystal phase at particular degrees was not as high as the standard hydroxyapatite data due to the incomplete formation of apatite crystal within 24 hours—the stretching vibration presence in the FTIR graph at 1400 cm-1 proven to be fluorapatite cement. Conclusions: Fluorapatite cement as an anti-caries agent can be fabricated through the mixing process of DCPA, CaCO3, and CaF2 powders with NaH2PO4 solution.